2021
DOI: 10.1101/2021.10.22.465153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aurora B/C-dependent phosphorylation promotes Rec8 cleavage in mammalian oocytes

Abstract: To generate haploid gametes, cohesin is removed in a stepwise manner from chromosome arms in meiosis I and the centromere region in meiosis II, to segregate chromosomes and sister chromatids, respectively. Meiotic cohesin removal requires cleavage of the meiosis-specific kleisin subunit Rec8 by the protease Separase[1, 2]. In yeast, Rec8 is kept in a non-phosphorylated state by the action of PP2A-B56, which is localised to the centromere region, thereby preventing cohesin removal from this region in meiosis I[… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A recent study showed that phosphorylation of the cohesin protein REC8 by AURKB/C kinases is required for chromosome segregation in mouse oocytes, suggesting that deregulation of REC8 phosphorylation contributes to meiotic chromosome segregation errors. [ 25 ] Meanwhile, TEX19.1 (Testis expressed 19.1) was discovered as a previously unknown regulator of the cohesin complex by regulating UBR (ubiquitin‐protein ligase E3 component N‐recognin 2) protein activity to maintain the acetylation of the cohesin protein SMC3 in mouse oocytes. The acetylation of SMC3 is essential for establishment and maintain of sister chromatid cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that phosphorylation of the cohesin protein REC8 by AURKB/C kinases is required for chromosome segregation in mouse oocytes, suggesting that deregulation of REC8 phosphorylation contributes to meiotic chromosome segregation errors. [ 25 ] Meanwhile, TEX19.1 (Testis expressed 19.1) was discovered as a previously unknown regulator of the cohesin complex by regulating UBR (ubiquitin‐protein ligase E3 component N‐recognin 2) protein activity to maintain the acetylation of the cohesin protein SMC3 in mouse oocytes. The acetylation of SMC3 is essential for establishment and maintain of sister chromatid cohesion.…”
Section: Introductionmentioning
confidence: 99%